Removal of toxic wastes from the effluents of fish processing industries through bioremediation - Anuja Madhavan V. (KUFOS, 2019)
The waste water discharges from fishing harbour, fish market and the fish processing plants are the major sources of organic load in the natural water bodies leading to eutrophication and environmental pollution. Waste water samples (effluent) collected from Chambakara, Thevara fish market and seafood processing plant at Kochi, Kerala were subjected to the process of bioremediation by aquatic plants serves as an effective method to improve the physicochemical parameters of effluent water. Nitrogenous compounds such as ammonia, nitrate and nitrite found to be higher in effluent water. Similarly the phosphate and silicate content was also high in industry sample. Upon treatment there was an increase in DO and reduction in nitrogenous compound but in case of ammonia the reduction was from 2-10%. The volatilization of the ammonia was observed in indoor experiment. Ammonia, nitrate and nitrite contents in the industrial effluent were found to be higher than the market sample. The ammonia content in the effluent water which was found to be very high with a value of 3.95mg/l. The Ammonical nitrogen showed compariteively less absorption (5-15%) with highest decline in TR2 E. crassiceps. The overall decline of nitrite ranged from 24 to 47% with higher efficiency by T2 E. crassiceps followed by P. straitoes. There was a gradual decline of phosphate ranged between 50-55% after 10 DAT. Maximum changes was observed in silicate content showing decline between 44-91% with TR2 showed highest decline of silicate 91% followed by 90% in TR3 88% in TR1 and 44% in control. Eichhornia crassipes is effective in improving the quality of effluents from fish processing industry and the market samples whereas Pistia stratiotes could able to reduce the phosphate contamination. The industrial effluent sample was very rich in protein and lipid. Protein content of 1718mg/l and lipid of 2388mg/l from the effluent of the fish processing industry is generally discarded back into the waste stream, resulting in the loss of valuable components, especially soluble proteins with good functional and nutritional properties. Recovering proteins and lipid would reduce the negative environmental effect and generate potential profits.